Sarcophagid flies (Diptera) from sinop, state of Mato Grosso, Brazil - H. de Souza Lopes; Rita Tibana (Memorias do Instituto Oswaldo Cruz, 1982)
In Sinop, State of Mato Grosso, Brazil, for the first time specimens of Euboettcheria, with seven species, are dominant (54.39%) among the Sarcophagid flies. Two new species of Euboettcheria (alvarengai and roppai) and females of known species are described and figured. Notochaeta sinopi n.sp. and Sinopiella rufopilosa n. gen., n. sp. are also described. As espécies do gênero Euboettcheria são, pela primeira vez, observadas como dominantes (54.39%), com sete espécies em Sinop, Estado de Mato Grosso, Brasil. Duas novas espécies (alvarengai e roppai) e fêmeas de espécies conhecidas foram descritas e figuradas. Notochaeta sinopi n. sp. e Sinopiella rufopilosa n. gen., n. sp. são também descritos.